Cardiometabolic Risk is Positively Associated with Underreporting and Inversely Associated with Overreporting of Energy Intake Among European Adolescents: The Healthy Lifestyle in Europe by Nutrition in Adolescence (HELENA) Study. Issue 3 (20th January 2021) - González-Gil, Esther M; Huybrechts, Inge; Aguilera, Concepción M; Béghin, Laurent; Breidenassel, Christina; Gesteiro, Eva; González-Gross, Marcela; de Henauw, Stefaan; Kersting, Mathilde; Donne, Cinzia Le; Manios, Yannis; Marcos, Ascensión; et al.
ABSTRACT: Background: Dietary misreporting is the main limitation of dietary assessments and has been associated with BMI during youth. However there are no prior studies assessing misreporting and cardiometabolic risks (CMRs) in adolescence. Objectives: To examine the associations between dietary misreporting and CMR factors in adolescents and to assess the potential bias in the association between CMR and energy intake (EI) driven by dietary misreporting. Methods: Two 24-hour dietary recalls were obtained from 1512 European adolescents (54.8% girls) aged 12.5–17.5 years. Physical activity was measured by accelerometry. Cut-offs suggested by Huang were applied to identify misreporters. Height, waist circumference (WC), the sum of 4 skinfold thicknesses, diastolic blood pressure (DBP), systolic blood pressure (SBP), and cardiorespiratory fitness (CRF) measurements were taken and serum triglycerides and total-/high-density lipoprotein cholesterol ratio were analyzed. A sex- and age-specific clustered CMR score ( n = 364) was computed. Associations were investigated by multilevel regression analyses adjusting for age, sex, center, socioeconomic status, and physical activity. Results: Underreporting (24.8% adolescents) was significantly ( P < 0.05) associated with a higher WC, waist-to-height ratio (WHeR), and sum of skinfold thickness, whereas overreporting (23.4% adolescents) was significantly associated with a lower WC, WHeR, sum of skinfold thickness, and SBP. Associations between CMR factors and EI were significantly affected by misreporting, considering various approaches. Significant, positive associations became inverse after adjusting for misreporting for WC and WHeR. The opposite was true for the sum of skinfold thickness, SBP, and CMR score. The associations between EI and DBP and CRF did not remain significant after adjusting for misreporting. Conclusions: CMR factors differed among misreporting groups, and both abdominal and total fat mass indicators were more strongly associated with all forms of misreporting than was BMI. Moreover, misreporting seems to bias EI and CMR associations in adolescents. Therefore, energy misreporting should be taken into account when examining diet-CMR associations.